Screening of Hepatitis B and C Viruses in Patients before Ocular Surgical Procedures (Medical Forum Monthly, 2024)
Objective: To screen and see the incidence of hepatitis B and C among patients before ocular surgical procedures.Study Design: Prospective / Observational StudyPlace and Duration of Study: This study was conducted at the Department of Ophthalmology, Dow University Hospital (ojha campus) of Dow International Medical College, Karachi, Pakistan from May 2014 to December 2014.Patients and Methods: 223 patients above the age of 18 years were screened for hepatitis B and C before going ocular surgery by immune-chromatographic method (ICT).The patients who were positive for hepatitis were further confirmed by Enzyme Linked Immunosorbent Assay (ELISA).Results: Total number of patients screened was 223. 11 (4.93%) patients were positive for hepatitis B and C, out of which 2(0.9%) were hepatitis B positive and 9(4%) were hepatitis C positive. Prevalence among male patient was 6.97% while among female was 2.12%.Conclusion: The eye patients show high incidence of hepatitis B and C. Therefore, it is mandatory for all patients who need ocular surgery to be screened by serological test for hepatitis B and C preoperatively.